Analysis of fluid balance and urine values in elite soccer players: impact of different environments, playing positions, sexes, and competitive levels - Sebastiá-Rico, J.; Soriano, J. M.; Sanchis-Chordà, J.; García-Fernández, Á. F.; López-Mateu, P.; de la Cruz Marcos, S.; Martínez-Sanz, J. M. (Nutrients, 2024)
Exercise can disrupt the fluid balance, hindering performance and athlete health. Limited data exist on fluid balance responses in varying climates, sexes, and ages. This study aimed to measure and compare fluid balance and urine values among elite soccer players during training at high and low temperatures, examining the differences between sexes, playing positions, and competitive levels within men`s soccer. During the 2022-2023 competitive season, a descriptive observational study was conducted on 87 soccer players from an elite Spanish soccer team. The study found that none of the groups exceeded weight loss values of 1.5% of their body mass. Additionally, the soccer players studied experienced higher weight loss, fluid intake, and a higher sweat rate (SR) during summer training compared to winter training. During the summer, male U23-21 soccer players exhibited higher levels of weight loss, fluid intake, and a higher SR compared to female soccer players or the U19-17 male category. No significant differences were found between playing positions. In conclusion, differences in the fluid balance were observed based on the climatic conditions, competitive level, and sex.